Goldfish (Carassius auratus) larviculture in biofloc systems: Level of Artemia nauplii, stocking density and concentration of the bioflocs - Besen K.P.* (2021)
© 2021 Elsevier B.V.The present study evaluated the use of a biofloc system (BFT) for the larviculture of goldfish (Carassius auratus). Two experiments were carried out, of which the first evaluated two culture systems (BFT and clear water) and three densities of Artemia nauplii (100, 200 and 300 nauplii larvae−1). The second experiment evaluated two concentrations of total suspended solids (150 and 300 mg L−1) and three densities of goldfish larvae (10, 20, and 30 larvae L−1). Both trials lasted 15 days and were performed in a completely randomized design (DIC) in a 2 × 3 factorial scheme, with six replicates per treatment. The cultivation with the bioflocs showed the best growth and survival of goldfish larvae. The higher supply level of Artemia nauplii (300 nauplii larvae−1) led to the best growth of the goldfish larvae when compared to the lower densities of nauplii, regardless of the cultivation system. The concentration of total suspended solids of up to 300 mg L−1 had no adverse effect on the growth performance of the animals. Best growth results in the biofloc system were obtained with 10 larvae L−1. The increase in stocking density reduced growth of the larvae but resulted in higher biomass.